2016
DOI: 10.3346/jkms.2016.31.9.1355
|View full text |Cite
|
Sign up to set email alerts
|

Signal Detection of Adverse Drug Reaction of Amoxicillin Using the Korea Adverse Event Reporting System Database

Abstract: We conducted pharmacovigilance data mining for a β-lactam antibiotics, amoxicillin, and compare the adverse events (AEs) with the drug labels of 9 countries including Korea, USA, UK, Japan, Germany, Swiss, Italy, France, and Laos. We used the Korea Adverse Event Reporting System (KAERS) database, a nationwide database of AE reports, between December 1988 and June 2014. Frequentist and Bayesian methods were used to calculate disproportionality distribution of drug-AE pairs. The AE which was detected by all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…A signal detection of adverse drug reaction identified by WHO-UMC reported a potential sub-group at risk which suggested that males may be at increased risk for drug induced aseptic meningitis with the use of amoxicillin and amoxicillin in combination with clavulanic acid 42 . Another 12 new signals were detected in Korea on the use of amoxicillin including ineffective amoxicillin 43 , however, the chirality factor was not reported to be associated with the new signals. In addition, a concern on safety of ceftriaxone has been reported for both adults and children 44,45 .…”
Section: Discussionmentioning
confidence: 94%
“…A signal detection of adverse drug reaction identified by WHO-UMC reported a potential sub-group at risk which suggested that males may be at increased risk for drug induced aseptic meningitis with the use of amoxicillin and amoxicillin in combination with clavulanic acid 42 . Another 12 new signals were detected in Korea on the use of amoxicillin including ineffective amoxicillin 43 , however, the chirality factor was not reported to be associated with the new signals. In addition, a concern on safety of ceftriaxone has been reported for both adults and children 44,45 .…”
Section: Discussionmentioning
confidence: 94%
“…The KAERS database was developed by KIDS in 2012 to manage AE reports effectively. This computerized AE reporting system includes voluntary reporting by healthcare workers and the general public, as well as mandatory reporting by manufacturers for serious and unexpected events, using a standardized form [11]. Reports from the Korean Regional Pharmacovigilance Centers accounted for 71.5% (163,676 reports) of the KAERS database, and among these, hospitals/clinics accounted for the majority.…”
Section: Methodsmentioning
confidence: 99%
“…Medical practices have proved that surveillance and learning from patient safety incidents can reduce the odds of making mistakes, and by doing so, improve patient safety. Given that, many countries have developed their reporting systems and have carried out a series of research works 810. In China, the National Patient Safety Incidents Reporting System (NPSIRS) was rolled out from early 2012.…”
Section: Introductionmentioning
confidence: 99%